Ethical contexts and theoretical issues : essays in ethical thinking - Sia, Santiago (Cambridge Scholars Pub., 2010)
"Ethics has become a particularly relevant topic for discussion and a subject for serious study. It has a very long tradition, of course; but nowadays one hears frequently of the need, because of abuses or concerns, to formulate and adopt ethical codes in various areas or professions. This book aims to make a philosophical contribution to the discussions and debates on the topic. Compared to the traditional approach to the philosophical study of ethics, however, this book adopts a different strategy. It shows that such ethical thinking, in the concrete particulars, originates in various academic and professional contexts, among others. But inasmuch as theoretical issues require wider and more intensive attention, it argues that ethical thinking needs to be pursued further and that it can be aided by philosophical investigations. In its concluding chapters the book presents an alternative foundation for ethical decision-making. Philosophically grounded, it moves away from an individualistic ethical perspective to a relational one that has been shaped through dialogue with the various contexts in which ethical thinking arises."--Publisher's description